A Decision Support System In Determining The Admission Of New Student To TJKT Vocational Program At SMK Negeri 3 Bengkulu City Using SAW Method - Wijaya Anugerah Kusuma; Indra Kanedi; Prahasti Prahasti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The admissions of New student are an important process that determines the quality of students at a school. Until now, the selection process for prospective students at SMK Negeri 3 Bengkulu City, particularly in the Computer Network and Telecommunications Engineering (TJKT) program, has been carried out manually, which is time-consuming and prone to subjectivity in decision-making. To overcome this, this study aims to develop a Decision Support System (DSS) for new student admissions using Simple Additive Weighting (SAW) method, which can help schools determine eligible prospective students more quickly, accurately, and objectively. This system was developed using PHP programming language with MySQL database and tested using the black box method to ensure that all functions ran as required. The results of testing 15 prospective new student data for the 2025/2026 academic year showed that the system was able to display the calculation results automatically and provide recommendations on eligibility for admission. From this test, 7 prospective students were accepted and 8 prospective students were not accepted..